Colposcopic triage methods for detecting cervical intraepithelial neoplasia grade 3 after cytopathological diagnosis of low-grade squamous intraepithelial lesion: a systematic review on diagnostic tests - Corrêa, Flávia de Miranda; Russomano, Fábio Bastos; Oliveira, Caroline Alves de (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: The age-stratified performance of the oncogenic HPV-DNA (human papillomavirus deoxyribonucleic acid) test for triage of low-grade squamous intraepithelial lesions (LSIL) requires investigation. The objective of this study was to evaluate and compare the age-stratified performance (cutoff point: 35 years) of oncogenic HPV-DNA testing and repeated cytological tests, for detecting cervical intraepithelial neoplasia grade 3 (CIN3), in order to triage for LSIL. DESIGN AND SETTING: Systematic review. Studies were identified in nine electronic databases and in the reference lists of the articles retrieved. METHODS: The eligibility criteria consisted of initial cytological findings of LSIL; subsequent oncogenic HPV-DNA testing and repeated cytological tests; and CIN3 detection. The Quality Assessment of Diagnostic Accuracy Studies (QUADAS) guidelines were used for quality assessment. Qualitative information synthesis was performed. RESULTS: Out of 7,776 studies, 284 were identified as pertinent and three fulfilled the eligibility criteria. The CIN3 prevalence ranged from 6% to 12%. The HPV-DNA positivity rate ranged from 64% to 83%; sensitivity for CIN3 detection ranged from 95.2% to 100%; and specificity was available in two studies (27% and 52%). The sensitivity of repeated cytological tests, in relation to the threshold for atypical squamous cells of undetermined significance (ASCUS), was available in two studies (33% and 90.8%); and specificity was available in one study (53%). CONCLUSIONS: Currently, there is no scientific evidence available that would prove that colposcopic triage using oncogenic HPV-DNA testing to detect CIN3 performs better than repeated cytological tests, among women with LSIL aged 35 years and over.